IOT based Advanced Black Box with Accident Detection and Location Tracing with Engine Auto Engine Turn off - sulthana, Neha; M.C, Chinnaaiah.; K, Nandan.; Keerthi, T.; Sirisha, T. (International Journal of Engineering and Technology, 2018)
In this system, with the help of the far spread Black Box we are able to gather the information on the subject of the accidents and also the safety information. In past if the information is required after the accidents takes place investigators try to find out the accident related clues non-systematically. A systematic black box method is proposed which collects and stores the information while driving. In addition, whenever the vehicle meets with accident, the accident switch attached to the controller gates pressed and immediately sends location of the vehicle with longitude and latitude to the registered phone numbers of family which are feed in the system. This helps in taking immediate action when accident occurs. The location of the vehicle traced through GPS and the traced data is saved in the SD card where this system acts as block box for a vehicle as well as. A user can find his vehicle location just by sending SMS to it if it got theft, the user can turn off the engine anywhere from the world just by sending SMS using preferred match word. This Entire data can be monitored using NODEMCU on the webpage.
Keywords: AVR; GSM; GPS; LCD; SD card; Accident switch; Node MC.